The Prevalence of Prenatal Opioid and Other Drug Use in Utah - Buchi, Karen F.; Suarez, Carla; Varner, Michael W. (American Journal of Perinatology, 2013)
Objectives Determine the prevalence of prenatal opioid and other drug positivity among women delivering infants in Utah and compare the findings with national data.Study Design Umbilical cord tissue samples and nonidentifiable demographic data were collected anonymously in 13 labor and delivery units throughout Utah. Samples were analyzed for opioids, amphetamines, cannabinoids, cocaine, phencyclidine, barbiturates, benzodiazepines, propoxyphene, and alcohol biomarkers.Results Fifty-eight (6.8%) of 850 umbilical cord samples were positive for one or more substances. Opioids were the most frequently detected drugs (4.7%). Fewer samples were positive for alcohol (0.4%), methamphetamine (0.1%), cocaine (0.1%), and marijuana (0.4%).Conclusion Opioids were the most frequently detected drugs at delivery. Although some of the samples positive for opioids might have been a result of intrapartum exposure, a significant number were positive for opioids that are not given during labor. This parallels the increasing nonmedical use of prescription pain medications in the general population and has important implications for neonates because of the potential for significant morbidity secondary to neonatal abstinence syndrome.
Keywords: prenatal; drug use; opioids; umbilical cord drug screening